Wastewater Generation and Their Biological Treatment (Eurasian Scientific Herald, 2023)
The article provides information on the generation and biological treatment of wastewater from high-water plants using pistia (Pistia stratiotes L) and eichhornia (Eichhornia crassipes Solms)